Laxative Effects of a Standardized Extract of Dendropanax morbiferus H. Léveille Leaves on Experimental Constipation in Rats - Ju-Ryun Na (MDPI AG, 2021)
Background and Objectives: This study aimed at investigating the laxative effects of a standardized aqueous extract of Dendropanax morbiferus H. Lév. on two different constipation rat models. Materials and Methods: Animal studies were conducted with low-fiber diet-induced and loperamide-induced constipation animal models, and isolated colons were used in ex vivo analysis to determine the changes in colonic motility caused by D. morbiferus H. Lév. leaf extract (DPL). Results: The results showed that DPL administration significantly improved certain reduced fecal parameters (number, weight, and water content of the stools) in a both low-fiber diet and loperamide-induced constipation models without adverse effects of diarrhea. The laxative effect of DPL was confirmed to improve the charcoal excretion time upon DPL treatment in a low-fiber diet or loperamide-induced constipation model through gastrointestinal (GI) motility evaluation using the charcoal meal test. In addition, when DPL was administered to RAW264.7 cells and loperamide-induced constipation model rats, the production of prostaglandin E2 (PGE2) increased significantly in cells and tissue. Furthermore, DPL dose-dependently stimulated the spontaneous contractile amplitude and frequency of the isolated rat colon. Conclusion: Although our study did not provide information on the acute or chronic toxicity of DPL, our results demonstrated that DPL can effectively promote defecation frequency and rat colon contraction, providing scientific evidence to support the use of DPL as a therapeutic application. However, further toxicity studies of DPL are needed prior to the initiation of clinical trials and clinical applications.